Conservation planning and Indigenous governance in Australia's Indigenous Protected Areas. Issue 5 (21st June 2016) - Godden, Lee; Cowell, Stuart
Abstract : Indigenous Protected Areas (IPAs) recognize that "country" constitutes land and waters that have enduring cultural, social, and economic linkages for Aboriginal and Torres Strait Islander peoples that extend over millennia, and which are critical to sustainable Indigenous futures. Within Australia's conservation system, IPAs become part of the National Reserve System (NRS) when Indigenous peoples voluntarily announce their intention to manage "country, " in accordance with their law, custom, and culture, and consistently with national and international conservation guidelines. The NRS requirement is that land is managed "in perpetuity" which highlights a potential tension between with the conservation goals and the voluntary character of IPAs. Ecological restoration in IPAs also raises contested ideas about what is "natural, " the relevant "baseline" for restoration, and what are the objectives to be achieved—ecological or cultural sustainability? Experience from Healthy Country Planning in IPAs indicates that restoration of traditional owner decision‐making, as well as respectful use and valuing community knowledge, is central to the sustainability of outcomes. Ecological restoration is most effectively achieved by restoring governance processes that support Indigenous peoples given the inseparability of cultural, social, economic, and ecological objectives.